Treatment of Thyroid Tumor Japanese Clinical Guidelines - Takami, Hiroshi; Ito, Yasuhiro; Noguchi, Hitoshi; Yoshida, Akira; Okamoto, Takahiro; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2013)
Creating clinical guidelines is a modern trend. Published studies pertaining to a given theme are collected, their credibility evaluated, and then treatment options in the form of evidence-based guidelines are offered. There are a number of guidelines for the treatment of thyroid tumors that have established positions in clinical practice in North America and in Western European countries. In Japan, however, where radioisotope facilities are of limited availability, treatment plans for differentiated thyroid cancer differ considerably from those of America and Europe, and the associated clinical guidelines need modification before they can be adopted. In addition, although thyroid tumor is a common disease in endocrine practice, its management can differ even among specialists. Thus, a Japanese clinical guideline for the treatment of thyroid tumor was desired by many clinicians. As a combination of evidence-based and consensus-based guidelines for the treatment of thyroid tumor, this book offers alternatives to conventional approaches in the West. Ultimately, the authors hope the guideline will lead to the best possible treatment for patients all over the world in the not-distant future.
Keywords: Medicine; Endocrinology; Oncology; Surgery; Medicine & Public Health; Oncology; Endocrinology; Surgery